2021
DOI: 10.31557/apjcp.2021.22.1.45
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Barriers to Colorectal Cancer Screening among Eligible Adults in Qatar and Its Predictors: A Cross-Sectional Study

Abstract: Background: In Qatar, colorectal cancer (CRC) is the second most common cancer and is projected to be more than triple by 2035. Therefore, CRC periodic screening is vitally important because early detection will improve the success of treatment. In 2016, Qatar established a population-based screening program for CRC targetting average-risk adults. This study aimed to determine the perceived barriers to undergo CRC screening in eligible adults in Qatar and the associated factors. Methods: This was a cross-secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…Results from our literature review echoed our qualitative findings regarding attitudes and behaviors; however, some studies identified in the literature review were completed in other Middle Eastern countries, rather than Egypt (Al-Dahshan et al, 2021;Qumseya et al, 2014;Tfaily et al, 2019). Other studies reported that physicians in Egypt tend to not order tests or follow recommended screening schedules, similar to other countries in the region (Mosli et al, 2017;Muliira et al, 2016).…”
Section: Resultssupporting
confidence: 70%
“…Results from our literature review echoed our qualitative findings regarding attitudes and behaviors; however, some studies identified in the literature review were completed in other Middle Eastern countries, rather than Egypt (Al-Dahshan et al, 2021;Qumseya et al, 2014;Tfaily et al, 2019). Other studies reported that physicians in Egypt tend to not order tests or follow recommended screening schedules, similar to other countries in the region (Mosli et al, 2017;Muliira et al, 2016).…”
Section: Resultssupporting
confidence: 70%
“…The Emotion domain was well-defined among the public at the individual level. Fear, as it relates to test results, undergoing screening, endoscopic procedures, and potential pain from screening are all factors that were commonly identified at this level ( 15 , 17 , 18 , 20 , 21 , 23 , 25 , 31 , 34 , 36 , 39 , 40 , 42 , 46 ). Additionally, anxiety, shyness, embarrassment/shame, weariness of screening being conducted by a provider of the opposite sex, and a ‘bad feeling’ were also described in the literature ( 15 , 17 , 18 , 21 , 23 , 25 , 31 , 46 ) ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Despite the significant investments in healthcare, sufficient attention has not been paid to predictive diagnosis and targeted prevention. Despite the availability of sufficient finances, Qatar has low awareness regarding CRC prevention and treatment among residents, and reluctance towards screening and a lack of reminders from healthcare providers are some other screening barriers[ 45 ].…”
Section: Discussionmentioning
confidence: 99%